2012
DOI: 10.2174/156800912799277476
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Angiogenesis for Treatment of NSCLC Brain Metastases

Abstract: Lung cancer is the leading cause of cancer-related mortality worldwide, and non-small cell lung cancer (NSCLC) accounts for about 85% of all new lung cancer diagnosis. The majority of people with NSCLC are unsuitable for surgery since most patients have metastatic disease at diagnosis. About 60% of brain metastases arise from lung cancer. Therapeutic approaches to brain metastases include surgery, whole brain radiotherapy (WBRT), stereotactic radiosurgery, chemotherapy and new biologic agents. Angiogenesis is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
27
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 72 publications
0
27
0
Order By: Relevance
“…It is known that central nervous system (CNS) bleeding in patients with BM is an important complication. The rate of the CNS bleeding is different across the type of tumor: 1-7% in lung cancer and 70% in renal cancer (13). On the basis of these observations patients with BM are frequently not candidate to clinical studies with anti-vascular endothelial growth factor (VEGF) therapy.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that central nervous system (CNS) bleeding in patients with BM is an important complication. The rate of the CNS bleeding is different across the type of tumor: 1-7% in lung cancer and 70% in renal cancer (13). On the basis of these observations patients with BM are frequently not candidate to clinical studies with anti-vascular endothelial growth factor (VEGF) therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Occurrence of BMF-NSCLC is associated with a very poor prognosis: median survival of untreated patients is about 1 month [1, 6, 8, 10, 11, 15, 17, 18, 21, 22] and of those receiving palliative corticosteroid treatment slightly over 2 months [17, 18]. Palliative whole brain radiotherapy (WBRT) prolongs median survival to 3–6 months [8, 10, 17].…”
Section: Introductionmentioning
confidence: 99%
“…The following methods are used in the treatment of BMF-NSCLC: surgery, SRS, WBRT, systemic treatments (chemotherapy, immunotherapy) and various combinations of these methods [1, 2, 46, 8, 9, 11, 12, 1719, 26, 28–35]. In general, local (surgery, SRS) [1, 4, 6, 8, 17, 18, 28–30, 35] or regional (WBRT) [1, 4, 19, 28–30, 33–35] treatment is preferred, including combination of surgery and radiotherapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, exploratory analyses from studies involving NSCLC patients with undiagnosed or previously treated BM at enrolment concluded that wBM patients are at similar risk of cerebral haemorrhage, regardless of bevacizumab treatment [10][11][12][13][14][15][16] . Furthermore, the BM contraindication was removed from the EU Summary of Product Characteristics in 2009 after the submission of comprehensive safety data [17] .…”
mentioning
confidence: 99%